2022-RA-1524-ESGO COVID-19 pandemic impact on the availability and implementation of cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS+HIPEC) procedures in patients with peritoneal carcinomatosis at the Wroclaw comprehensive cancer centre – a single-centre study. (20th October 2022) - Szewczyk, Krzysztof; Jedryka, Marcin; Bebenek, Marek
Abstract : Introduction/Background: 'The impact of the COVID-19 pandemic on the oncological care system' report shows that the number of new diagnoses of malignant neoplasms in Poland has decreased by 20% and there has been a decrease by 10–15% in the area of oncological surgery procedures (https://www.zwrotnikraka.pl/influencing-pandemic-covid-19-na-system-oncological-care/). It is also known CRS+HIPEC procedures in the treatment of patients with primary and secondary peritoneal neoplasms have been performed in Poland in insufficient amounts for many years (http://www.chirurgia-onkologiczna.pl/images/files/hipec.pdf). The aim of the study was to analyse the changes in the availability and implementation of CRS+HIPEC procedures performed at the Wroclaw Comprehensive Cancer Center (WCCC) Poland, during the COVID-19 pandemic. Methodology: Demographic, clinical, oncological and technical aspects database of all CCCW patients undergoing the CRS+HIPEC procedure was created. Statistical analysis of the data was carried out using the Statistica version 12.5 (StatSoft) program, with particular emphasis on the period of the COVID-19 pandemic (from 03.2020). Results: In the period from 01.2014 to 04.2022, a total of 232 CRS+HIPEC procedures were performed at CCCW, on average 28 per year (range 20–37). During the COVID-19 pandemic (from 03.2020), after the initial complete suspension of CRS+HIPEC procedures (03–05.2020), their dynamic growth occurred – 72 procedures were performed in the period 06.2020 – 04.2022 in total. The main indications were ovarian (40%) and colorectal (39%) cancers. During the COVID-19 pandemic, the Clavien-Dindo grade III and IV complication rate (14%) did not change, and there were no perioperative deaths recorded. Conclusion: In the era of the COVID-19 pandemic, CRS+HIPEC procedures remain a safe and promising therapeutic option for selected patients with primary and secondary peritoneal cancers.